Understanding Career Commitment In Healthcare: Integrating Self-Efficacy, Motivation, And Employee Engagement - Abdul Gofur Taufik; Mirwan Surya Perdhana; Fuad Mas’ud; Dili Puspa Sri Wahyuningsih; Adhyasti Rinenggautami (Yayasan Darussalam Bengkulu, 2026)
Background: Healthcare organizations face growing challenges in maintaining employees’ long-term career commitment due to high job demands, emotional pressure, and workforce instability. Career commitment is essential for ensuring service quality and organizational sustainability in hospital settings. This study aims to examine the effects of self-efficacy and motivation on career commitment and to investigate the mediating role of employee engagement among healthcare professionals at Rodliyah Achid Islamic Hospital. Method: This study employed a quantitative research design using a census approach involving 86 healthcare employees at Rodliyah Achid Islamic Hospital in Indonesia. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 to evaluate the relationships among self-efficacy, motivation, employee engagement, and career commitment. Results: The findings reveal that self-efficacy and motivation have significant positive effects on career commitment. In addition, both variables significantly improve employee engagement, which subsequently has a positive impact on career commitment. The study also confirms that employee engagement partially mediates the relationships between self-efficacy and career commitment, as well as between motivation and career commitment. These results indicate that employees with greater confidence in their abilities and stronger work motivation tend to demonstrate higher career commitment through increased psychological engagement at work. Conclusion: This study contributes to the career commitment literature by providing empirical evidence from the healthcare sector that self-efficacy, motivation, and employee engagement are critical factors in strengthening long-term professional commitment. The findings highlight the importance of simultaneously enhancing employees’ psychological confidence, work motivation, and engagement to sustain career dedication and organizational stability in healthcare environments.